Why Student Teachers Major in English Education: An Analysis of Motives for Becoming Future Teachers - Masbirorotni, Masbirorotni; Mukminin, Amirul; Muhaimin, rer. Net.; Habibi, Akhmad; Haryanto, Eddy; Hidayat, Marzul; Marzulina, Lenny; Harto, Kasinyo; Erlina, Dian; Kamil, Dairabi (Revija za elementarno izobraževanje, 2020)
This study explores the major factors that motivated 1139 student teachers at six teacher training institutions from the intake years 2015 to 2018 to enrol in English education programs. The result of quantitative descriptive analysis showed that in extrinsic motives, out of twenty-three motive statements, the mean scores of ten motive statements were included in the medium interpretation, followed by intrinsic motives with the mean scores of only three statements included in the medium interpretation out of thirteen motive statements, and in altruistic motives, of seventeen motive statements, the mean scores were included in the low interpretation.
Keywords: altruistic motives, extrinsic motives, intrinsic motives, student teachers